FABCOR : a study of a multi-racial labour force - Doxey, G V (George Victor) (School of Economics, 2016)
This thesis is largely a descriptive study of a single factory, FABCOR. I have tried to avoid the temptation to draw generalisations from a single case history and where I have deviated from FABCOR to illuminate any particular point, it has been with the aid of material I have gathered in other enquiries. The pattern of labour relations in South Africa bears the bold imprint of multi-racialism. Apart from the general economic problems of labour, in the Union the labour market is complicated, and to a large extent conditioned by such multi-racial characteristics as differing environmental backgrounds of the workers, educational and aptitudinal disparities, and colour sensitivity manifesting itself in legal and customary sanctions. FABCOR which employs workers of all races provides ample material for research in this field. In examining its problems I have sought to throw some light on those influences which affect the ability and the willingness of South African labour to provide productive services. What is the attitude of the non-European to work and what are his qualifications? Is he conscious of his role in the productive process or does he regard himself merely as a tool in the economy, with little ambition or prospect for the future? How do his background and training equip him to play a useful role in industry? In the answers to these questions lies an important clue to the future course - and pace - of industrial development in South Africa.